2011
DOI: 10.1371/journal.pone.0024194
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Tyrosine Kinase FGFR2b/KGFR Controls Early Differentiation of Human Keratinocytes

Abstract: The FGFRs trigger divergent responses, such as proliferation and differentiation, and the cell type as well as the context-dependent signaling are crucial for the functional outcome. The FGFR2b/KGFR is expressed exclusively on epithelial cells and plays a key role in skin homeostasis. Here we analyzed in vitro the role of KGFR in the early differentiation of keratinocytes modulating its expression by KGFR cDNA transient transfection or KGFR siRNA microinjection and inducing a synchronous wave of differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 43 publications
(85 reference statements)
8
55
0
Order By: Relevance
“…The possible crucial role of FGF7 and its receptor in epithelial cell homeostasis has been widely proposed 25 - 27 . In particular, we have recently demonstrated that the FGF7-mediated activation of FGFR2 triggers early differentiation in keratinocytes during the switch from undifferentiated to differentiating cells, 28 the same step in which it has been recently proposed that autophagy might represent a crucial event for cell commitment to differentiation 29 . Moreover, FGFR2 expression and signaling regulate the phagocytic process in keratinocytes 30 .…”
Section: Introductionmentioning
confidence: 86%
“…The possible crucial role of FGF7 and its receptor in epithelial cell homeostasis has been widely proposed 25 - 27 . In particular, we have recently demonstrated that the FGF7-mediated activation of FGFR2 triggers early differentiation in keratinocytes during the switch from undifferentiated to differentiating cells, 28 the same step in which it has been recently proposed that autophagy might represent a crucial event for cell commitment to differentiation 29 . Moreover, FGFR2 expression and signaling regulate the phagocytic process in keratinocytes 30 .…”
Section: Introductionmentioning
confidence: 86%
“…p38-MAPK regulates a wide range of targets, including other kinases/phosphatases, transcription factors and RNA-binding proteins (Cuadrado and Nebreda, 2010). Moreover, p38-MAPK is a downstream target of FGFR2b, a crucial receptor for epithelial differentiation in the skin and prostate (Belleudi et al, 2011;Heer et al, 2006;Lamb et al, 2010). Despite these findings, how p38-MAPK expression in prostate epithelial cells drives differentiation, including its relevant targets, remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a stratified epithelium consisting of suprabasal luminal cells sitting on top of basal cells. p38-MAPK is a known downstream target of KGF-to-FGFR2 signaling and is implicated in epithelial differentiation in several tissue types, including prostate (Belleudi et al, 2011;Lamb et al, 2010). Four different genes encode p38-MAPK isoforms: MAPK14 ( p38α), MAPK11 ( p38β), MAPK12 ( p38γ) and MAPK13 ( p38δ).…”
Section: Introductionmentioning
confidence: 99%
“…It is supposed to be secreted from fibroblasts mainly in the stroma and bind to KGF Receptor (KGFR), which has been detected only on the surface of epithelial cells (Lin et al, 2010). KGFR still exists in hair follicles and is expressed in hair follicle epithelial cells and KGF in dermal papilla cells, which declares that KGF is mediated through paracrine (Belleudi et al, 2011). Koria et al (2011) showed KGF was expressed in normal skin and was induced upon injury.…”
Section: Keratinocyte Growth Factor (Kgf)mentioning
confidence: 99%